Practical challenges of introducing WHO surgical checklist: UK pilot experience. (13th January 2010) - Vats, A; Vincent, C A; Nagpal, K; Davies, R W; Darzi, A; Moorthy, K
Abstract : The WHO checklist has the potential to reduce preventable adverse events in surgery. But A Vats and colleagues ' experience suggests that a careful and rigorous implementation plan is required to ensure that the checklist is used routinely and correctly